Advancements in Numerical Methods for Solving Nonlinear Hyperbolic PDEs- A Multidisciplinary Approach (International Journal of Food and Nutritional Sciences, 2023)
Recent advancements in numerical methods for solving nonlinear hyperbolic partial differential equations (PDEs) have demonstrated their significance across various multidisciplinary domains. These advanced techniques have the potential to revolutionize the way we model complex phenomena. By combining high-order schemes, adaptive mesh refinement, and innovative algorithms, these methods offer improved accuracy and computational efficiency, making them well-suited for handling intricate geometries, steep gradients, and real-world nonlinear phenomena. The collaboration across mathematics, physics, engineering, and computational sciences has played a pivotal role in their development, ensuring that they are not just theoretically sound but also versatile and applicable to a wide range of problems. While challenges exist, such as implementation complexity and problem-specific nature, the future of this field holds promise for further innovations, including algorithmic improvements, parallelization for high-performance computing, and continued interdisciplinary collaboration, ultimately contributing to more accurate and efficient numerical simulations in diverse scientific and engineering domains.